Modeling and software implementation of manufacturing costs in additive manufacturing. (May 2021) - Yi, Li; Ehmsen, Svenja; Glatt, Moritz; Aurich, Jan C.
Abstract: Quantification and analysis of manufacturing costs in additive manufacturing (AM) are important research tasks, since materials and machines for AM are relatively expensive. To enable the cost estimation in AM, a number of studies have focused on the development of cost estimation software tools for AM. However, these studies mainly focused on single AM systems and materials pre-selected for individual cases. The literature still lacks of a more general perspective on the cost factors and cost structure in different AM processes. Addressing this issue, this paper contributes a general cost model for AM processes and the development of a cost estimation application (App) based on the model. The developed App covers a variety of AM materials and systems. In order to validate the usability of the App, three use cases are performed. The result of the use cases demonstrates that the App, as well as the underlying cost model, is a powerful tool for estimating and assessing the build cost of AM in different design issues.